Functional group selective STM imaging in self-assembled monolayers: Benzeneselenol on Au(111) - Azzam, Waleed; Zharnikov, Michael; Rohwerde, Michael; Bashir, Asif (Applied surface science, 2017)
Benzeneselenol (PSe) self-assembled monolayers (SAMs) formed on Au(111) substrate by the immersion procedure with an immersion time of 24h and 4 weeks were studied by high-resolution scanning tunneling microscopy (STM). The short molecular rows, which have been previously attributed to irregular translational domains, were found to be regularly repeated within a single domain in the SAMs fabricated upon the immersion for 4 weeks, forming adlayer structure with a very large unit cell. This structure could be assigned as a (27×5) superlattice (α phase) containing 36 molecules in the oblique unit cell. This phase coexisted with a different phase having a commensurate (83×4) superstructure (β phase) containing 28 protrusions per rectangular unit cell. Analysis of the STM images suggested that each PSe molecule in the β phase was imaged not as one but as a pair of protrusions, which were attributed to the benzene ring and the selenium headgroup of the PSe molecule. At the given molecular length, the spacing between the protrusions defined the molecular tilt, allowing us to derive the orientation of the SAM constituents directly from the STM image.
First published: 31 August 2017